Analisis Kesalahan Berbahasa Tataran Sintaksis dalam Buku Teks Bahasa Indonesia Kelas VIII SMP/MTs Kurikulum 2013 Terbitan Kemendikbud - Rahmadani, Suci; S., Ermawati (UIR PRESS, 2021)
Indonesian language textbooks issued by the Ministry of Education and Culture are certainly better than those written individually. However, it turns out that there are still and the authours found language errors in thhem, especially at the syntactic level. The prolems in this researchhh are (1) how are the language erros in the syntactic level of the phrase field contained in the Inonesian language texsbook for class VIIISMP/MTs curriculum 2013 published by the Ministry of Education and Culture? class VIIISMP/MTs curriculum 2013 published by the Ministry of Education and Culture?. The purpose of this study is to describe, analyze, interpret, and conclude language errors at the syntactic level in the field of phrases and sentences contained in the Indonesian language textbooks for VIIISMP/MTs curriculum 2013 published by the Ministry of Education and Culture. The theory used in this research is the theory proposed by Setyawati (2010). The method used is content analysis method. The approach in this research is qualitative research. The results of this study are: (1) language errors at the syntactic level in the phrase field into 5 data found, among others: the influence of regional languages, the use of excessive or redundant elements, the use of excessive or redundant elements, the use of inappropriate prepositions. (2) language errors at he syntactic level in the verse field were found, including: illogical sentences, and the use of foreign terms.